Perception of Institutional Quality Difference and Return Migration Intention: The Case of the Vietnamese Diaspora - Ngoc Thi Minh Tran; Michael P. Cameron; Jacques Poot (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2021)
This study examines whether the perception of difference in institutional quality between OECD destination countries and Vietnam, and the stated importance attached to such difference, influences Vietnamese migrants' intention to return home. We use data from a web-based survey (N = 159) that we conducted in 2016. The countries covered capture about 90% of the Vietnamese diaspora in the world. We find, by means of weighted logistic regression analysis with a range of measures of institutional quality, that migrants who perceive a larger institutional quality difference are less likely to have the intention to return. However, there is considerable heterogeneity by gender. Women are, if they attach importance to institutional quality, particularly concerned about control of corruption, while the between-country difference in government effectiveness and regulatory quality matters to men. Concerns about a lack of voice & accountability; and about political instability & the presence of violence/terrorism deter return migration of both genders.
Keywords: F22; O15; 330; Return migration intention; institutional quality; perception; heterogeneity; Vietnam